ANALISIS DRUG RELATED PROBLEMS (DRPs) PENGGUNAAN ANTIPSIKOTIK PADA PASIEN SKIZOFRENIA DI RUMAH SAKIT JIWA PROVINSI LAMPUNG JANUARI-JUNI 2024: DRUG RELATED PROBLEMS (DRPs) ANALYSIS OF ANTIPSYCHOTIC USE IN SCHIZOPHRENIA PATIENTS AT THE MENTAL HOSPITAL OF LAMPUNG PROVINCE JANUARY-JUNE 2024 - Hijrah, Hijrah; Wahyuni, Novita Tri; Isbiyantoro, Isbiyantoro; Sari, Wulan (JFL : Jurnal Farmasi Lampung, 2025)
Schizophrenia is severe mental disorder that affects an individual’s thought, feelings, and behavior. Antipsychotics are the primary treatment for schizophrenia and used for a long preiod of time which increases the risk of Drug Related Problems (DRPs) and cause ineffective therapeutic results.  The purpose of this study was to analyze the incidience of DRPs on the use antipsychotic in scizhoprenia patients at The Mental Hospital Of Lampung Province January-June 2024. This research study is a descriptive study with purposive sampling technique. The number of samples used was 86 samples of schizophrenia in patients at Mental Hospital Of Lampung Province in January-June 2024.  The results showed that the characteristics of schizophrenia patiens based on gender were 77 men (89,5%) and 9 women (10,5%).  Characteristic based on age are26-35 years old 35 people (40,7%).  The Characteristics of the most patients occupations were not working 68 people (79,1%). The most prevalent kind of schizophrenia patients was paranoid schizophrenia as 82 cases (94,2%).  The most prescribed drugs for schizophrenia patients were risperidone 82 prescriptions, chlorpromazine 70 prescriptions, and trihexyphenidyl 86 prescriptions. The incidence of DRPs in the category of inappropriate drug combinations was 86 cases (100%), drug dose too low was 23 cases (27%), drug dose too high 0%, and inapproprate of drug administration was 0%. The conclusion of this study is the precentage of Drug Related Problems (DRPs) in schizophrenia patients at the Mental Hospital Of Lampung Province is 32%.   Keywords : Antipsychotics, DRPs, Schizophrenia